ANALISIS PENGUATAN PENDIDIKAN KARAKTER DAN IMPLIKASINYA TERHADAP PENDIDIKAN ISLAM - Khairani Rangkuti; Khaerul; Taufik Abdillah Syukur; Rifky Aditya Ramadhan (Yayasan Baitul Hikmah al-Zain, 2024)
The aim of this research is to analyze the enhancement of character education and its implications on Islamic education. Character education plays a crucial role in shaping a generation with noble character and integrity. Within the context of Islamic education, the instilled character values align with religious teachings that prioritize morals and ethics. This research employs a qualitative method with a literature study approach to investigate relevant literature. The findings demonstrate that the strengthening of character education has a substantial impact on the development of Islamic education, encompassing cognitive, affective, and psychomotor aspects.